Staple-type sweet potatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Staple-type sweet potatoes Although the sweet potato already ranks as the number six crop produced throughout the world, its full potential has yet to be realised. A recent development in this direction has been the introduction of what is being...